(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Student satisfaction is an essential aspect of any successful educational program. This paper examines the level of satisfaction of students in advanced English for an Effective Communication Course offered at Gulf University with the learning experience. Specifically, the paper explores the factors that contribute to student satisfaction with learning, such as course content, teaching methods, and course instructor. The study was conducted over one academic semester during the Spring of the academic year 2022/2023, and quantitative and qualitative data were collected from 20 students who participated in the course through a survey of student’s satisfaction with the course. The results indicated that students were highly satisfied with the English for Effective Communication Course, and identified course content, teaching methods, and feedback as key factors contributing to their satisfaction. All the survey questions scored an average above 4.50 out of 5.00 on the Gulf University course survey questionnaire, and show a high level of satisfaction. The paper concludes with recommendations for educators on how to design and deliver courses that satisfy students’ needs.